From War to Hope: Coping Strategies of the Members of the Autodefensas Unidas de Colombia that Reintegrated to Society (2018)
This paper is a product of the exploratory study “Personal strategies in men and women, excombatants of the Autodefensas Unidas de Colombia and the resignification of their life project”,carried out in the city of Medellín, Colombia, based on the testimonies of two ex-combatants. It identifies and analyses the coping strategies incorporated in the process that have influenced the resignification of their life experiences in the war. The methodology applied was case studies with ex-combatants, a man and a woman, of the Autodefensas Unidas de Colombia (AUC) who completed their reintegration process, promoted by the Colombian Agency for Reintegration and who voluntarily participated in the investigation. With their testimonies, an approach to some of the experiences shared by men and women in the war was possible, and the influence of socio-historical and gender conditions to reconstruct a life project in legality was made evident. Finally, some proposals are formulated for the interventions of ex-combatants of the armed conflict in Colombia as contributions to the current reincorporation process.